Dry electrode and preparation method thereof, and battery

By embedding a metal mesh as a sandwich material in the dry electrode, the problem of insufficient lateral tensile strength of the dry electrode is solved, which significantly improves the cycle stability, safety and service life of the battery, and improves the conductivity and stress distribution of the electrode.

CN119764335APending Publication Date: 2025-04-04SHENZHEN QINGYAN ELECTRONIC TECH CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510246101.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-04
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The dry electrode has shortcomings in terms of lateral tensile strength, resulting in problems such as damage to the electrode structure, attenuation of battery capacity, poor cycle stability, increased safety risks, reduced production efficiency and increased costs.

Method used

During the manufacturing process of the dry electrode, a layer of metal mesh is added as the interlayer material, and the metal mesh is uniformly embedded in the electrode film through double-stage rolling composite technology to form a composite material structure to enhance the lateral tensile strength of the electrode.

Benefits of technology

Through the addition of the metal mesh, the lateral tensile strength of the electrode is significantly improved, the cycle stability, safety and service life of the battery are improved, and the conductivity and stress distribution of the electrode are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119764335A_ABST
    Figure CN119764335A_ABST
Patent Text Reader

Abstract

The embodiments of the present invention disclose a dry electrode and a preparation method and a battery, wherein the dry electrode includes an electrode membrane, wherein a metal mesh is embedded in the middle of the electrode membrane. In the manufacturing process of the dry electrode, the present invention adds a layer of metal mesh as an interlayer, similar to the steel bars in reinforced concrete, to enhance the transverse tensile strength of the electrode. The present invention provides structural support through the metal mesh to enhance the overall strength and stability of the electrode membrane when subjected to stress. As a "skeleton" reinforcement material, the metal mesh can effectively reduce the crack generation and peeling problems of the electrode membrane, and enhance the cycle performance, safety and service life of the battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of new energy batteries, and in particular to a dry electrode and a preparation method thereof, and a battery. Background Art

[0002] In the manufacturing process of lithium-ion batteries, the traditional wet electrode preparation process has always occupied the mainstream position. This process dissolves the active material, conductive agent and binder in a solvent to form a uniform slurry, which is then coated on the metal current collector. After a series of steps such as drying and compaction, the electrode is finally obtained. However, the limitations of the wet process are gradually emerging, especially in terms of environmental protection and cost control. Common solvents such as NMP (N-methylpyrrolidone) have excellent solubility properties, but their volatility and toxicity problems pose potential risks to worker health and environmental safety. In addition, the wet process has complicated steps, and the drying process not only consumes a lot of energy, but also prolongs the production cycle, increases the process complexity and equipment maintenance costs. Therefore, environmentally friendly and low-cost production methods have become a hot topic in current research, and dry electrode preparation technology has emerged.

[0003] The key to dry electrode preparation technology is to eliminate the use of organic solvents, thereby avoiding solvent pollution and solvent recovery problems in wet processes. In early studies, scholars tried to use solid binders, such as polytetrafluoroethylene (PTFE), whose excellent chemical stability and mechanical properties make it an ideal binder material. By mixing PTFE powder with active materials and processing them under high temperature and high pressure conditions, these materials can be effectively combined into electrode membranes. Compared with wet processes, dry processes have significant advantages such as simplified production processes, reduced energy consumption, and reduced waste gas emissions. At the same time, researchers are gradually exploring other types of binders, such as hot melt binders. These binders can become fluid when heated, fully mixed with active materials, and form a stable electrode structure after cooling. Although the use of such binders requires attention to their high temperature resistance and chemical stability, they provide an effective solution for the further application of dry processes and promote the development of lithium battery production technology.

[0004] Although dry electrodes have many advantages in the manufacturing process, such as simplified process, energy saving and environmental protection, their lack of transverse tensile strength has gradually become a key issue limiting their widespread application. The production method of dry electrodes relies on the close combination of active materials and solid binders through heating and pressing. Although this method can effectively reduce the use of solvents, its performance in tensile strength, especially transverse tensile strength, is not satisfactory.

[0005] First, the active materials and binders in the dry process are not fully dissolved and evenly dispersed by the solvent, which makes the bonding between the materials weak, especially in the lateral direction of the electrode film. This low bonding means that the electrode is prone to cracking or peeling during use, especially during high-rate charge and discharge or cyclic use. Insufficient lateral tensile strength may lead to damage to the electrode structure, thus affecting the battery's service life and cycle stability.

[0006] Secondly, due to the limited control of temperature and pressure during the manufacturing process of dry electrodes, the microstructure of the electrode is not as uniform as that of the wet process. This uneven microstructure directly leads to unstable tensile strength of the electrode material when subjected to force, especially in the lateral area of ​​the electrode, where the strength of the local area is weak and it is more likely to cause material breakage or damage.

[0007] In addition, due to the limited selection of binders and conductive agents in the dry process, and the relatively small amount of binder, the overall structure of the electrode lacks sufficient toughness in the lateral direction. Although the binder can provide a certain degree of adhesion, its usage and distribution method make it difficult to form a uniform network structure throughout the electrode. Therefore, when stretched by external force, the electrode has poor lateral tensile strength and is prone to cracks or peeling.

[0008] In general, the problem of poor transverse tensile strength of dry-process electrodes is mainly due to uneven bonding of materials and instability of microstructure. This not only affects the cycle stability of the battery, but may also reduce the safety and service life of the battery. Therefore, when further promoting the dry process, how to improve the transverse tensile strength of the electrode is still a technical challenge that needs to be solved.

[0009] The poor transverse tensile strength of dry electrodes may lead to the following effects: (1) Destruction of electrode structure.

[0010] When the battery expands or contracts during the charge and discharge process, if the transverse tensile strength of the electrode is insufficient, it may cause cracks or peeling of the electrode film. Especially during high-rate charge and discharge, the electrode material will be subjected to greater stress. At this time, poor transverse tensile strength will cause cracks on the surface or inside of the electrode, affecting the structural integrity of the battery.

[0011] (2) Battery capacity decay accelerates.

[0012] Cracks or peeling of the electrode will lead to the loss of active materials, thus affecting the capacity retention of the battery. Especially after multiple charge and discharge cycles, the cracked or peeled parts will continue to expand, eventually leading to a decrease in the effective capacity of the battery and a significant shortening of the cycle life.

[0013] (3) Poor battery cycle stability.

[0014] Poor transverse tensile strength makes it difficult for the electrode material to maintain a stable structure during repeated charge and discharge of the battery. As the electrode is gradually damaged, the internal resistance of the battery increases and the cycle performance decreases, resulting in poor performance and high capacity decay after multiple cycles.

[0015] (4) Increased safety risks.

[0016] If the cracks in the electrode material develop to a certain extent, it may cause a short circuit inside the battery, or even cause safety problems such as thermal runaway. Cracks or peeling may expose active materials, increasing the risk of thermal runaway or short circuit in the battery, thus affecting the safety of the battery.

[0017] (5) Reduce production efficiency and increase costs.

[0018] Poor transverse tensile strength of electrode materials may lead to more defective products in the production process, increasing the scrap rate of production, which in turn leads to increased manufacturing costs. In addition, battery failure or substandard performance requires additional testing and repair, further reducing production efficiency.

[0019] (6) Affects the mechanical strength and stability of the battery.

[0020] In some application scenarios that require high mechanical strength and stability, such as electric vehicles and high-power equipment, the poor lateral tensile strength of dry electrodes may affect the mechanical properties of the battery, causing the battery to deform or break easily during use, affecting the operation of the equipment. Summary of the invention

[0021] The technical problem to be solved by the embodiments of the present invention is to provide a dry electrode and a preparation method thereof, and a battery, so as to improve the transverse tensile strength of the electrode.

[0022] In order to solve the above technical problems, an embodiment of the present invention provides a dry electrode, including an electrode film, wherein a metal mesh is embedded in the middle of the electrode film.

[0023] Furthermore, the metal mesh is a copper mesh or an aluminum mesh.

[0024] Furthermore, the metal mesh adopts a rectangular grid structure and is densely arranged in the MD direction.

[0025] Furthermore, a plurality of blind holes are provided on the main body surface of the metal mesh.

[0026] Furthermore, the blind holes are evenly distributed, and the spacing between the blind holes is in the range of 2-5 μm.

[0027] Furthermore, the blind hole is a circular blind hole with a hole diameter of 10-30 µm and a depth of 5-10 µm.

[0028] Furthermore, the surface of the metal mesh is nickel-plated, and the thickness of the coating is in the range of 5-10 μm.

[0029] Accordingly, an embodiment of the present invention further provides a method for preparing a dry electrode, comprising: Step 1: Prepare a metal mesh and electrode materials; Step 2: The three-layer structure of electrode material-metal mesh-electrode material is simultaneously fed into a roller press for double-stage roller pressing to obtain a dry electrode, so that the metal mesh is evenly embedded in the electrode film as an interlayer material.

[0030] Furthermore, the electrode material is composed of a mixture of an active material, a conductive agent and a binder, the active material is a positive electrode material or a negative electrode material, and the thickness of the electrode material ranges from 50 to 300 μm.

[0031] Correspondingly, an embodiment of the present invention further provides a battery, comprising the above-mentioned dry electrode.

[0032] In the manufacturing process of the dry electrode, the present invention adds a layer of metal mesh as an interlayer, similar to the steel bars in reinforced concrete, to enhance the transverse tensile strength of the electrode. The present invention provides structural support through the metal mesh to improve the overall strength and stability of the electrode film when subjected to force. The metal mesh, as a "skeleton" reinforcement material, can effectively reduce the crack generation and peeling problems of the electrode film, and improve the cycle performance, safety and service life of the battery. The beneficial effects of the present invention are: (1) Enhance the mechanical strength of the electrode.

[0033] The copper mesh / aluminum mesh of the present invention can play the role of "skeleton" to enhance the overall structural strength of the electrode membrane, especially in the lateral direction. Similar to the tensile strength of reinforced concrete, the copper mesh can effectively share external forces in the electrode membrane to prevent the electrode membrane from cracking or breaking due to stress concentration during use. This can significantly improve the tensile strength of the electrode, especially during high-rate charge and discharge.

[0034] (2) Improve the stability of the electrode.

[0035] The copper mesh / aluminum mesh of the present invention can provide a stable support structure, making the electrode more stable during the expansion or contraction process during charge and discharge. The good conductivity and moderate flexibility of copper can also help the electrode material maintain good integrity, avoiding crack expansion or active material shedding due to excessive stress between electrode layers.

[0036] (3) Improve the cycle performance of the battery.

[0037] The present invention can reduce the deformation of the electrode during multiple charge and discharge cycles by enhancing the tensile strength of the electrode film, thereby reducing the rate of battery capacity decay and performance degradation. Stronger transverse tensile strength helps the electrode maintain better structural stability, reduces the risk of active material shedding, and thus improves the cycle life of the battery.

[0038] (4) Improve battery safety.

[0039] The present invention enhances the mechanical stability of the electrode by using the copper mesh / aluminum mesh, which can reduce the risk of short circuit and thermal runaway caused by electrode deformation or breakage. In particular, under high-power discharge or high-temperature environments, the enhanced structural strength can effectively avoid instability inside the battery, thereby improving the overall safety of the battery.

[0040] (5) Improve conductivity.

[0041] The copper mesh / aluminum mesh of the present invention as a conductive material may improve the overall conductivity of the electrode, especially when the battery is discharged at a high rate, it can effectively reduce the internal resistance and improve the discharge performance and power density of the battery. The addition of the copper mesh may reduce the demand for other conductive agents (such as carbon black, carbon nanotubes, etc.), thereby reducing material costs.

[0042] (6) Improve stress distribution.

[0043] The copper mesh / aluminum mesh of the present invention can effectively disperse the stress inside the electrode film, so that the stress is evenly distributed in the electrode film, preventing excessive stress in a local area from causing electrode damage. This uniform distribution of stress helps to improve the overall performance and reliability of the battery.

[0044] The present invention performs laser drilling on the surface of the copper mesh / aluminum mesh to further enhance the mechanical properties of the electrode sheet, improve the conductivity, and optimize the heat exchange performance, and the surface of the copper mesh / aluminum mesh is nickel-plated to enhance corrosion resistance and conductivity. The microporous structure of the present invention can significantly increase the contact area between the copper mesh surface and the electrode membrane. In the manufacture of dry electrodes, the electrode membrane is attached to the surface of the copper mesh by pressing and other methods, and the micropores can provide more attachment points for the membrane. This "micro hook" effect allows the electrode membrane to be more firmly attached to the grid, thereby improving the lateral tensile strength of the membrane and reducing the shedding and peeling of the membrane during use. The micropores of the present invention can help disperse the local stress of the electrode membrane when it is stressed, avoid stress concentration in a small area, reduce the rupture or peeling of the membrane, and play a role in stress dispersion. The microporous structure has a potential positive effect on the conductivity of the copper mesh. By increasing the effective contact area of ​​the mesh surface, the micropores can improve the conduction path of the current to a certain extent, reduce resistance, and improve the conductivity of the electrode. Dry electrodes accumulate heat during operation, especially at high power output and high current density. Heat dissipation is critical to the stability and life of the battery. The microporous copper mesh helps improve heat conduction and heat dissipation.

[0045] The nickel plating layer of the present invention enhances the corrosion resistance of the metal surface. The nickel layer can form a protective barrier to prevent the chemical substances in the electrolyte from directly reacting with the copper mesh, thereby preventing oxidation, corrosion and degradation of the metal. Nickel itself has good electrical conductivity, and the nickel plating layer can improve the electrical conductivity efficiency of the copper mesh surface. The nickel layer can optimize the conduction of current by increasing the conductive path on the copper mesh surface, and in the dry electrode membrane, ensure that the current flows evenly in the mesh. BRIEF DESCRIPTION OF THE DRAWINGS

[0046] Figure 1 Schematic diagram of the structure of a dry electrode according to an embodiment of the present invention.

[0047] Figure 2 Schematic diagram of the structure of the metal mesh according to an embodiment of the present invention.

[0048] Figure 3 It is a schematic structural diagram of the dry electrode preparation according to an embodiment of the present invention.

[0049] Figure 4 It is a schematic diagram of the capacity retention rate of each embodiment of the present invention and the comparative example after several cycles.

[0050] Description of Figure Numbers 1. Upper membrane, 2. Metal mesh, 3. Lower membrane, 4. Current collector. DETAILED DESCRIPTION

[0051] It should be noted that, in the absence of conflict, the embodiments in the present application and the features in the embodiments may be combined with each other. The present invention is further described in detail below in conjunction with the drawings and specific embodiments.

[0052] In the embodiments of the present invention, if there are directional indications (such as up, down, left, right, front, back, etc.), they are only used to explain the relative position relationship, movement status, etc. between the components under a certain specific posture (as shown in the accompanying drawings). If the specific posture changes, the directional indication will also change accordingly.

[0053] In addition, in the present invention, the descriptions of "first", "second", etc. are only used for descriptive purposes and cannot be understood as indicating or implying their relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" or "second" may explicitly or implicitly include at least one of the features.

[0054] The dry electrode of the embodiment of the present invention comprises an electrode film. A metal mesh is embedded in the middle of the electrode film, and the electrode film is attached to the current collector. That is, the dry electrode of the present invention has a three-layer structure. Please refer to Figure 1 , from top to bottom are the upper membrane, the metal mesh, and the lower membrane, and the lower membrane is attached to the current collector.

[0055] As an implementation method, the metal mesh is a copper mesh or an aluminum mesh. In specific implementation, during the dry electrode manufacturing process, the copper mesh or aluminum mesh is used as an interlayer material and embedded in the middle layer of the electrode membrane to form a composite material structure, which is similar to the reinforcement effect of reinforced concrete. This structure enhances the lateral tensile strength of the electrode membrane and improves the cycle stability and safety of the battery.

[0056] Please refer to Figure 2 As an implementation method, the metal mesh adopts a rectangular grid structure and is densely arranged in the MD direction (Machine Direction, ‌ refers to the mechanical direction of the material, usually refers to the longitudinal or flow direction of the material). Such a design can more effectively disperse the transverse tensile stress generated by the membrane during the charging and discharging process, thereby improving the crack resistance and tensile strength of the electrode membrane.

[0057] As an implementation method, a plurality of blind holes are provided on the main body surface of the metal mesh. The blind holes are evenly distributed, and the spacing between the blind holes ranges from 2 to 5 μm. The blind holes are circular blind holes with an aperture of 10 to 30 μm and a depth of 5 to 10 μm. In a specific implementation, laser etching can be used to process the surface of the copper mesh / aluminum mesh to form a large number of tiny blind holes. This structure has a very high surface area, significantly improves the performance of the metal surface, and improves the bonding force with the diaphragm. The copper mesh / aluminum mesh is also plated with a nickel layer to enhance corrosion resistance and conductivity.

[0058] As an embodiment, the surface of the metal mesh is nickel-plated, and the thickness of the coating is in the range of 5-10 µm. The nickel-plated layer enhances the corrosion resistance of the metal surface. The nickel layer can form a protective barrier to prevent the chemicals in the electrolyte from directly reacting with the copper mesh, thereby preventing oxidation, corrosion and degradation of the metal. Nickel itself has good electrical conductivity, and the nickel-plated layer can improve the electrical conductivity efficiency of the copper mesh surface. The nickel layer can optimize the conduction of current by increasing the conductive path on the surface of the copper mesh, and in the dry electrode membrane, ensure that the current flows evenly in the grid.

[0059] The method for preparing the dry electrode according to the embodiment of the present invention comprises: Step 1: Prepare a metal mesh and electrode materials; Step 2: The three-layer structure of electrode material-metal mesh-electrode material is simultaneously fed into a roller press for double-stage roller pressing to obtain a dry electrode, so that the metal mesh is evenly embedded in the electrode film as an interlayer material.

[0060] The present invention adopts a two-stage rolling (rough pressing + fine pressing) process in the dry electrode manufacturing process to embed the copper mesh / aluminum mesh into the electrode film as an interlayer material, thereby significantly improving the lateral tensile strength, cycle stability and high-rate discharge capability of the electrode film.

[0061] The specific preparation process of the present invention is as follows: 1. Raw materials preparation: (1) Electrode material: Dry electrode material is composed of a mixture of active material, conductive agent and binder, which is evenly mixed to form a free-flowing powder for subsequent roller pressing.

[0062] Active materials: such as positive electrode materials (LiFePO4, NCM, LCO) or negative electrode materials (graphite, silicon carbon).

[0063] Conductive agents: carbon black, carbon nanotubes (CNTs).

[0064] Binder: Polytetrafluoroethylene (PTFE) or other polymers.

[0065] Material thickness control: The thickness of the diaphragm is generally 50-300 µm.

[0066] (2) Strengthen the mesh material.

[0067] Copper mesh or aluminum mesh is used as reinforcement material according to the positive and negative electrode materials of the electrode to improve the lateral tensile strength of the electrode film.

[0068] Grid structure: Rectangular grid, dense in MD direction, such as a mm × b mm (a>b), which ensures enhanced strength without affecting the conductivity and ion transport of the electrode material.

[0069] Copper / Aluminum mesh thickness: 20-100 µm.

[0070] Copper mesh / aluminum mesh wire diameter: 50µm -1000µm.

[0071] Laser drilling is used to drill circular blind holes with an aperture of 10-30 µm on the surface of the copper mesh / aluminum mesh. The blind hole depth is 5-10 µm. The blind holes are evenly distributed with a spacing of 2-5 µm. The surface is nickel-plated with a coating thickness of 5-10 µm.

[0072] (3) Equipment preparation.

[0073] Roller press: controls pressure and temperature to make the grid evenly embedded in the electrode membrane.

[0074] Rewinding and unwinding device: ensures smooth transportation of the electrode film during rolling to prevent wrinkles or misalignment.

[0075] 2. Grid material alignment: In order to ensure the uniform distribution of the reinforcement grid, a synchronous feeding system is used to keep the copper mesh / aluminum mesh and the electrode film at the same tension and speed.

[0076] Feeding method: Automatic roll-to-roll alignment to avoid grid offset or overlap.

[0077] An optical sensor is used to detect the position to ensure that the grid is in the center of the electrode membrane.

[0078] Tension control: The copper mesh / aluminum mesh needs to maintain proper tension to prevent wrinkles or damage during the rolling process.

[0079] Use tension adjustment system for real-time monitoring and adjustment.

[0080] 3. Multi-layer composite roll-pressing film: The three-layer structure of electrode material-grid-electrode material is composited by roll pressing, so that the copper mesh / aluminum mesh is evenly embedded in the electrode film.

[0081] (1) Multilayer structure enters roller press: The upper electrode film, the middle copper mesh / aluminum mesh, and the lower electrode film, the three-layer structure enters the roller press synchronously to form a composite electrode film.

[0082] (2) Composite roll gap parameter optimization: Roll gap: 50-300 microns (larger roll gap avoids damage to the grid; smaller roll gap ensures bonding), adjusted according to electrode thickness.

[0083] Temperature: 60-110°C (moderate heating to increase binder activity) Avoid exceeding the material tolerance temperature to prevent damage to the active material or conductive agent.

[0084] Speed: 1-20 m / min (to ensure uniform rolling and prevent material dislocation). The mesh needs to be synchronized with the electrode film when entering to prevent stretching or folding.

[0085] (3) Compacting and bonding: Multi-pass rolling: Two-stage rolling (rough rolling + fine rolling) can be used to ensure that the grid is firmly embedded without damaging the electrode material. Please refer to Figure 3 . Example 1

[0086] The materials are mixed and evenly dispersed, the materials comprising: active material NCM, adhesive PTFE, conductive agent SP, and the mass percentages of the materials are 95%, 3%, and 2%, respectively. In this embodiment, the active material, the adhesive, the conductive agent, and the dispersant are mechanically mixed to form a uniform dry powder mixture. The evenly dispersed materials are subjected to fiberization treatment in a high-speed mixer to obtain the fiberized materials.

[0087] The fiberized material is placed in a multi-stage rolling device, and the film is formed by differential speed of the rollers to form a dry electrode self-supporting film. Copper mesh is used as a reinforcing material, and the grid structure is a rectangular grid with a size of 10 mm × 5 mm and a thickness of 15 µm. The three-layer structure of electrode material-grid-electrode material is composited by rolling to make the copper mesh / aluminum mesh evenly embedded in the electrode film. Adjust the composite roll gap A: 250 microns to avoid damaging the grid; adjust the composite roll gap B: 200 microns to ensure bonding. The roller press oil temperature is 100°C to increase the activity of the binder, and the composite speed is 5 m / min. The grid is synchronized with the electrode film when entering to prevent stretching or folding. Example 2

[0088] The materials are mixed and evenly dispersed, the materials comprising: active material graphite, adhesive PTFE, conductive agent sp, and the mass percentages of the materials are 95%, 3%, and 2%, respectively. In this embodiment, the active material, the adhesive, the conductive agent, and the dispersant are mechanically mixed to form a uniform dry powder mixture. The evenly dispersed materials are subjected to fiberization treatment in a high-speed mixer to obtain the fiberized materials.

[0089] The fiberized material is placed in a multi-stage rolling device, and the film is formed by differential speed of the rollers to form a dry electrode self-supporting film. Copper mesh is used as a reinforcing material, and the grid structure is a rectangular grid with a size of 10 mm × 4 mm and a thickness of 10 µm. The three-layer structure of electrode material-grid-electrode material is composited by rolling to make the copper mesh / aluminum mesh evenly embedded in the electrode film. Adjust the composite roll gap A: 150 microns to avoid damaging the grid; adjust the composite roll gap B: 120 microns to ensure bonding. The roller press oil temperature is 100°C to increase the activity of the binder, and the composite speed is 3 m / min. The mesh is synchronized with the electrode film when entering to prevent stretching or folding. Example 3

[0090] The materials are mixed and evenly dispersed, the materials comprising: active material LFP, adhesive PTFE, conductive agent SP, and the mass percentages of the materials are 95%, 3%, and 2%, respectively. In this embodiment, the active material, the adhesive, the conductive agent, and the dispersant are mechanically mixed to form a uniform dry powder mixture. The evenly dispersed materials are subjected to fiberization treatment in a high-speed mixer to obtain the fiberized materials.

[0091] The fiberized material is placed in a multi-stage rolling device, and the film is formed by differential speed of the rollers to form a dry electrode self-supporting film. Copper mesh is used as a reinforcing material, and the grid structure is a rectangular grid with a size of 15 mm × 5 mm and a thickness of 13 µm. The three-layer structure of electrode material-grid-electrode material is composited by rolling to make the copper mesh / aluminum mesh evenly embedded in the electrode film. Adjust the composite roll gap A: 200 microns to avoid damaging the grid; adjust the composite roll gap B: 180 microns to ensure bonding. The roller press oil temperature is 100°C to increase the activity of the binder, and the composite speed is 5 m / min. The grid is synchronized with the electrode film when entering to prevent stretching or folding. Example 4

[0092] The materials are mixed and evenly dispersed, the materials comprising: active material NCM, adhesive PTFE, conductive agent SP, and the mass percentages of the materials are 95%, 3%, and 2%, respectively. In this embodiment, the active material, the adhesive, the conductive agent, and the dispersant are mechanically mixed to form a uniform dry powder mixture. The evenly dispersed materials are subjected to fiberization treatment in a high-speed mixer to obtain the fiberized materials.

[0093] The fiberized material is placed in a multi-stage rolling device, and the film is formed by differential speed of the rollers to form a dry electrode self-supporting film. Copper mesh is used as a reinforcing material, and the grid structure is a rectangular grid with a size of 10 mm × 5 mm and a thickness of 12 µm. The three-layer structure of electrode material-grid-electrode material is composited by rolling to make the copper mesh / aluminum mesh evenly embedded in the electrode film. Adjust the composite roll gap A: 200 microns to avoid damaging the grid; adjust the composite roll gap B: 180 microns to ensure bonding. The roller press oil temperature is 100°C to increase the activity of the binder, and the composite speed is 5 m / min. The mesh is synchronized with the electrode film when entering to prevent stretching or folding.

[0094] Comparative Example 1 The materials are mixed and evenly dispersed, the materials comprising: active material NCM, adhesive PTFE, conductive agent SP, and the mass percentages of the materials are 95%, 3%, and 2%, respectively. In this embodiment, the active material, the adhesive, the conductive agent, and the dispersant are mechanically mixed to form a uniform dry powder mixture. The evenly dispersed materials are subjected to fiberization treatment in a high-speed mixer to obtain the fiberized materials.

[0095] The fiberized material is placed in a multi-stage rolling device, and the film is formed by differential speed of the rollers to form a dry electrode self-supporting film. The composite roll gap A is adjusted to 250 microns to avoid damaging the grid; the composite roll gap B is adjusted to 200 microns to ensure bonding. The roller press oil temperature is 100°C to increase the activity of the binder, and the composite speed is 5 m / min. The grid is kept synchronized with the electrode film when entering to prevent stretching or folding.

[0096] Comparative Example 2 The materials are mixed and evenly dispersed, the materials comprising: active material graphite, adhesive PTFE, conductive agent sp, and the mass percentages of the materials are 95%, 3%, and 2%, respectively. In this embodiment, the active material, the adhesive, the conductive agent, and the dispersant are mechanically mixed to form a uniform dry powder mixture. The evenly dispersed materials are subjected to fiberization treatment in a high-speed mixer to obtain the fiberized materials.

[0097] The fiberized material is placed in a multi-stage rolling device, and the film is formed by differential speed of the rollers to form a dry electrode self-supporting film. The composite roll gap A is adjusted to 150 microns to avoid damaging the grid; the composite roll gap B is adjusted to 120 microns to ensure bonding. The roller press oil temperature is 100°C to increase the activity of the binder, and the composite speed is 3 m / min. When the grid enters, it keeps synchronization with the electrode film to prevent stretching or folding.

[0098] The resistance test results of each embodiment and comparative example are shown in Table 1.

[0099]

[0100] The tensile strength test results of each embodiment and comparative example are shown in Table 2.

[0101]

[0102] The capacity retention rates of the embodiments and comparative examples after several cycles are as follows: Figure 4 shown.

[0103] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A dry electrode, comprising an electrode membrane, characterized in that: A metal mesh is embedded in the middle of the electrode film.

2. The dry electrode according to claim 1, characterized in that: The metal mesh is a copper mesh or an aluminum mesh.

3. The dry electrode according to claim 2, characterized in that: The metal mesh adopts a rectangular grid structure and is densely arranged in the MD direction.

4. The dry electrode according to claim 3, characterized in that: The main body surface of the metal mesh is provided with a plurality of blind holes.

5. The dry electrode according to claim 4, characterized in that: The blind holes are evenly distributed, and the spacing between the blind holes is in the range of 2-5 μm.

6. The dry electrode according to claim 5, characterized in that The blind hole is a circular blind hole with a hole diameter of 10-30 μm and a depth of 5-10 μm.

7. The dry electrode according to claim 3, characterized in that: The surface of the metal mesh is nickel-plated, and the thickness of the coating is in the range of 5-10 μm.

8. The method for preparing a dry electrode according to any one of claims 1 to 7, characterized in that: include: Step 1: Prepare a metal mesh and electrode materials; Step 2: The three-layer structure of electrode material-metal mesh-electrode material is simultaneously fed into a roller press for double-stage roller pressing to obtain a dry electrode, so that the metal mesh is evenly embedded in the electrode film as an interlayer material.

9. The method for preparing a dry electrode according to claim 8, characterized in that: The electrode material is composed of a mixture of an active material, a conductive agent and a binder. The active material is a positive electrode material or a negative electrode material. The thickness of the electrode material ranges from 50 to 300 μm.

10. A battery, characterized in that: It comprises the dry electrode as claimed in any one of claims 1 to 7.

Citation Information

Patent Citations

  • Preparation method of metal grid energy storage electrode

    CN110197892A

  • Composite metal foil, composite current collector and battery

    CN117239146A

  • Porous current collector and preparation method thereof, electrode plate and battery

    CN117976917A